Non-destructive honey adulteration fraud identification using hyperspectral imaging and deep learning - Muhammad Aqeel; Shahzad Hussain; Hammad Shahab; Khan Bahadar Khan; Kashif Munir (Food Control, 2026)

Beyond toxicity: Systems-level virulence of entomopathogenic fungi in termite social immunity - Hafiz Muhammad Usman; Hammad Hassan; Arshad Ali; Mohammad Mazharul Karim; Ali Hassan; Min Lu (Journal of Invertebrate Pathology, 2026)

Engineering MOF-on-MOF heterostructure for enhanced adsorption-assisted photocatalytic decontamination of carbamazepine: Kinetics, thermodynamic and pathway study - Muhammad Fayaz; Raza Ullah; Muzamil Ahmad; Ikram Ullah; Muhammad Rafiq; Ali Ahmad; Nasim Ullah; Faizan Jamil; Latif Ur Rehman; Hammad Ali; Bing Yu; Hailin Cong (Journal of Water Process Engineering, 2026)

Effect of predatory pressure on behavior of termite Reticulitermes chinensis - Hammad Hassan; Ali Hassan; Taqi Raza; Hafiz Muhammad Usman; Arshad Ali; Jinli Ding; Qiuying Huang; Min Lu (Journal of Insect Physiology, 2026)

Agrobacterium tumefaciens-mediated stable transformation of CP4 EPSPS gene conferring glyphosate resistance in Zea mays L - Muhammad Atif; Hammad Ahmed Abbasi; Muhammad Naveed Anjum (Ecological Genetics and Genomics, 2026)

Seroprevalence and risk factors of Mycobacterium avium subsp. paratuberculosis in dromedary camels of Southern Punjab, Pakistan - Aliza Ali; Mughees Aizaz Alvi; Muhammad Hammad Hussain; Muhammad Numan; Junaid Ahmad; Muzafar Ghafoor; Muhammad Khalid Mansoor; Muhammad Saqib (Tropical Animal Health and Production, 2026)

Bridging iron biofortification through integrative strategies from QTL mapping to regulatory-compliant genome editing - Sadia Hakeem; Safia Khushi; Muhammad Hammad Nadeem Tahir; Nadia Hussain Ahmed; Amna Bibi; Zulfiqar Ali (Cereal Research Communications, 2026)
Around two billion people are affected by iron (Fe) malnutrition globally, largely contributed by the consumption of cereal-based diets with low levels of iron and reduced bioavailability due to presence of inhibitor compounds like phenols and phytic acid. Among several methods of enhancing Fe content of staples, genetic biofortification is the most sustainable, and cost-effective method. Genetic biofortification through conventional breeding has succeeded in producing a number of cultivars marketed for high nutrition. However, this approach is limited due to the requirement of large genetic variation, long breeding time, phyto-availability of nutrients through soil only, gene targeting in compatible species only, lack of knowledge of QTL and genetic maps, environmental interactions, risk of linkage drag, and complex interrelations among nutrients as well as with other yield traits. With the advent of genomic approaches for targeted genetic manipulation, transgenic approach offers straightforward and robust techniques to genetically biofortify staples. While transgenic approaches to increasing Fe content have been helpful, genetically modified (GM) cultivars for staple crops may be delayed due to GM regulatory barriers. This chapter reviews the global status of Fe malnutrition, possible solutions to combat its deficiency, and bottlenecks towards Fe biofortification in staples. It also provides insights into transgenic approaches to address this issue as well as way forward to resolve the regulatory issues associated with GM crops by providing alternate options.

Exogenous salicylic acid induces GluA and PR1a defense genes and enhances tomato tolerance to combined salinity and bacterial canker stress - Jawad Ahmad; Hammad Ahmed Abbasi; Muhammad Atif; Sana Ullah; Abdullah Jalal; Zunaira Azam; Hafsa Bibi (Vegetos, 2026)

Sargassum muticum–derived biopolymer as a sustainable rheology and filtration modifier for high-temperature water-based drilling fluids - Precious Jumbo-Egwurugwu; Syahrir Ridha; Noridah Bt Osman; Okorie Ekwe Agwu; Muhammad Hammad Rasool; Shwetank Krishna (Sustainable Chemistry and Pharmacy, 2026)

Engineered Adsorbents for Microplastic Mitigation: From Interfacial Mechanisms to Scalable Environmental Perspectives - Hammad Sajjad; Waleed Altaf; Ramika Javaid; Tehreem Fakhra; Muhammad Hayat; Ammar bin Yousaf; Nadeem Raza; Suryyia Manzoor; Lilia Basilio de Caland (Journal of Environmental Chemical Engineering, 2026)

Structure-based immunopharmacological design of a multi-epitope vaccine candidate against Naegleria fowleri targeting TLR3: a pan-genomic and molecular dynamics approach - Rabia Faizan; Muhammad Naveed; Inmaculada Bellido Estevez; Hafiz Muzzammel Rehman; Ayesha Latif; Hafiz Muhammad Hammad; Abdul Rafay Khan; Seham O. Alsulami; Maha A. Aljumaa; Nantenaina Tombozara (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Prevalence of Vitamin D Deficiency in Ataxia-Telangiectasia: A Systematic Review and Single Arm Meta-Analysis - Muhammad Junaid Iqbal; Muteeba Azhar; Hammad Javaid; Amina Hassan; Ayesha Masood; Michele Menotta (The Cerebellum, 2026)

First principles investigation of hafnium-based perovskite hydrides XHfH3 (X: Li, Na, K, and Rb) for hydrogen storage applications - Abdellah Hammad; Djamel Bezzerga; Fouad Keramsi; Ikram Djebablia; Muhammad Zaman; Mamoun Fellah; El-Abed Haidar (Fuel, 2026)

Paleocene stratigraphic framework and sedimentary architecture in the Sub-Himalayan Fold and Thrust Belt of Muzaffarabad, Pakistan: Depositional environment, Biotas, Paleogeographic and Economic Significance - Syed Kamran Ali; Arslan Sajjad; George Kontakiotis; Hammad Tariq Janjuhah; Muhammad Saleem Mughal; Ahmer Bilal; Aamir Asghar; Aijaz Ali Halepoto; Evangelia Besiou; Assimina Antonarakou (Journal of Sedimentary Environments, 2026)

“Ondansetron augmentation for obsessive–compulsive disorder: A systematic review and meta-analysis of randomized placebo-controlled trials” - Anas Mohammad; Mohammad Ibrahim; Aneeq Mahmood Khan; Usama Pervaiz; Sarah Aijaz; Muhammad Hassnain Nasrullah; Hammad Jamil (European Journal of Clinical Pharmacology, 2026)

Geochemical and petrographic insights into the Lumshiwal Formation (NW Himalayas): implications for provenance, paleoclimate, and economic potential - Syed Nohman Gilani; Muhammad Saleem Mughal; Khawaja Umair Majeed; Hammad Tariq Janjuhah; Yongzhi Wang; Muhammad Atif Bilal; Ahmer Bilal; Syed Wajee-Ul Hassan Gillani; Muhammad Hafeez (Carbonates and Evaporites, 2026)

Insecticidal and antibacterial potential of Croton tiglium functionalized zinc oxide nanoparticles - Arshad Ali; Ali Hassan; Imran Afzal; Hammad Hassan; Kirshan Chand; Hafiz Muhammad Usman; Xiaolong Liu; Min Lu (International Journal of Tropical Insect Science, 2026)

Mechanistic and Data-Guided Design of Biochar Adsorbents for Gas Phase Pollution Control: A State-of-the-Art Review - Hammad Khan; Muhammad Arshad; Ahsan Jalal; Ubaid Khalid; Arslan Maqbool; Mahvash Ansari; Sajjad Hussain (Environmental Science and Pollution Research, 2026)

Biogenic silver-selenium nanocomposites as an effective and sustainable alternative for controlling citrus canker - Iqra Ilyas; Hammad Ul Hassan; Naveed Iqbal Raja; Zia-Ur-Rehman Mashwani; Hossam S. El-Beltagi; Muhammad Sheeraz Ahmad; Huma Qureshi; Tauseef Anwar; Muhammad Iqbal; Khalid H. Alamer; Nazih Y. Rebouh; Bakhrom Jobborov; et al. (Physiological and Molecular Plant Pathology, 2026)

Hypoxia adaptation in yak: Molecular, Genetic, and Physiological mechanisms of high-altitude resilience - Muhammad Wasique Shahid; Hammad Qaiser; Tanveer Hussain (Livestock Science, 2026)

Comment on “Prescribing patterns of glucagon like peptide-1 receptor agonists in the Swedish capital region: a register-based cross-sectional study” - Muhammad Salman; Muhammad Hammad Chola; Muhammad Hasan (European Journal of Clinical Pharmacology, 2026)

Competitive adsorption of antibiotics on waste-derived hybrid biochar: Performance, mechanism, and life cycle assessment - Ali Hamid; Ahsan Jalal; Muhammad Arshad; Muhammad Usama; Sajjad Hussain; Hammad Khan (Journal of Environmental Chemical Engineering, 2026)

Synergistic NiO-Pt heterostructure for enhanced hydrogen evolution: Boosting charge transfer and catalytic efficiency in alkaline media - Faria Rafique; Shahzad Ameen; Muhammad Hammad Ali; Aleena Tahir; Hamayal Shahzad; Amina Bhatti; Tanveer ul Haq; Mira Tul Zubaida Butt; Ammar Ahmed Khan; Saleh A. Ahmed; Irshad Hussain; Habib Ur Rehman (Fuel, 2026)

From half-cells to full-cells: across-scale comparative evaluation of lanthanum-based perovskites as high-performance anode materials for the oxygen evolution reaction - Blaž Toplak; Leon Müller; Ali Raza Khan; André Olean-Oliveira; Khuzaifa Yahuza Muhammad; Wang Feng; Raíssa Ribeiro Lima Machado; Da Xing; Mohammed-Ali Sheikh; Leander Kucklick; Ahammed Suhail Odungat; Adarsh Jain; et al. (Chemical Engineering Journal, 2026)

Moringa oleifera: a comprehensive review with special emphasis on phytochemistry - Muhammad Nazim; Wajid Raza; Faiz ul Hassan Nasim; Shazia Anjum; Hammad Ullah; Asif Nawaz; Muhammad Ayaz; Maria Daglia (Phytochemistry Reviews, 2026)

Sustainable biodiesel production via Alkanna tinctoria oil Conversion: A multi-method modeling approach utilizing crab shell-derived biochar catalysts - Ali Hamid; Hammad Khan; Arsalan Arif; Muhammad Arshad; Sajjad Hussain; Arslan Maqbool (Biomass and Bioenergy, 2025)

Runoff prediction under climatic variability using SWAT and machine learning models: a case study of the Hunza River basin - Muhammad Ghawas Kareem; Deshan Tang; Muhammad Farhan; Anis Ur Rehman Khalil; Hafiz Ahmad Hammad Abid (Theoretical and Applied Climatology, 2025)

Prediction of RNA editing sites and genome-wide characterization and identification of PERK gene family in Oryza sativa in response to salinity stress - Hafiz Muhammad Waqas; Muhammad Abu Bakar Saddique; Sajid Fiaz; Afnan A. Alnufaei; Muhammad Ali Sher; Badr Alharthi; Muhammad Hammad Nadeem Tahir; Mahmood Alam Khan; Shahmeer Shahid; Seung Hwan Yang (Genetic Resources and Crop Evolution, 2025)

Comment on “The effect of colchicine on coagulation in patients with chronic coronary disease who use vitamin K antagonists” - Rayan Babar; Muhammad Hammad Chola; Hanzlah Ahmed (European Journal of Clinical Pharmacology, 2025)

Circular Economy in Oilfield Systems: A Review of Culinary Waste Materials for Sustainable Drilling Fluids - Muhammad Hammad Rasool; Syahrir Ridha; Maqsood Ahmad; Numair Ahmed Siddiqui; Muhammad Khurram Zahoor; Azam Khan; Syed Abdul Moiz Hashmi (Circular Economy and Sustainability, 2025)

Dolomitized stromatolites during regressive-transgressive cycles in the Cambrian Abbottabad Formation, Pakistan: depositional environment, sequence stratigraphic significance, and paleogeographic implications - Syed Kamran Ali; George Kontakiotis; Tariq Mahmood; Muhammad Saleem Mughal; Hammad Tariq Janjuhah; Ahmer Bilal; Evangelia Besiou; Assimina Antonarakou (Carbonates and Evaporites, 2025)

Impact of Silicon Application on the Mineral Nutrient Profile and Fruit Quality of Mandarin Citrus Hybrid ‘Kinnow’ - Hafiz Faiq Bakhat; Muhammad Imran Razzaq; Muhammad Shafique Khalid; Sunaina Abbas; Natasha; Masood Iqbal Awan; Hasnain Anwar; Ghulam Mustafa Shah; Saira Afzal; Muhammad Rizwan Ashraf; Hafiz Mohkum Hammad (Applied Fruit Science, 2025)

Comprehensive study on efficient diclofenac sodium removal using walnut and pistachio shell activated carbon: ANN, kinetics, isotherms, thermodynamics and DFT calculations - Sinem Temiz Seymen; Handan Atalay Eroğlu; Elif Nihan Kadıoğlu; Muhammad Umar; Ali Hamid; Hammad Khan; Sajjad Hussain; Feryal Akbal (Biomass and Bioenergy, 2025)

Sustainable wastewater treatment via nitrogen/sulfur co-doped graphene composite: Mechanistic insights & process optimization - Humaira Seema; Muhammad Arshad; Arslan Maqbool; Sumbal Zeb; Ali Hamid; Muhammad Umar; Sajjad Hussain; Hammad Khan (Journal of Water Process Engineering, 2025)

Amino acid-modified nano-magnetite boosts okra [Abelmoschus esculentus (L.) Moench] yield and iron enrichment for improved nutrition - Maham Ishfaq; Fahad Shafiq; Sumera Anwar; Muhammad Iqbal; Syed Hammad Raza; Arslan Mahmood; Muhammad Ashraf (BioMetals, 2025)

Sedimentary architecture of the ediacaran mixed carbonate-siliciclastic system, NW arabian plate: Regionally extensive marine incursion or syntectonic fault-controlled basin? - Muhammad Hammad Malik; Arif Hussain; Ardiansyah Koeshidayatullah; Justin V. Strauss; Adhipa Herlambang; Abdulwahab M. Bello; Khalid Al-Ramadan (Precambrian Research, 2025)

Spatial distribution of mangrove soil organic carbon in Indus Delta, Pakistan: A multi-sensor remote sensing and machine learning approach - Hammad Gilani; Muddasir Shah; Shahzada Sohail Ijaz; Muhammad Asif; Abid Nazir; Niall P. Hanan (Estuarine, Coastal and Shelf Science, 2025)

Role of Bacillus pseudomycoides in Enhancing the Nutritional Profile of Five Vigna radiata (L.) Cultivars Under Saline Stress - Bushra Bilal; Zafar Siddiq; Tehreema Iftikhar; Muhammad Umar Hayyat; Hammad Majeed (Journal of Soil Science and Plant Nutrition, 2025)

Enhancing accuracy in flexural strength prediction of glass fibre-reinforced concrete via TPE-XGB algorithm and explainable machine learning - Muhammad Abdullah Khan; Anas Rahat Ullah; Danish Mukhtiar; Muhammad Shahid Siddique; Muhammad Hammad Iqbal; Waleed Bin Inqiad (Innovative Infrastructure Solutions, 2025)
This study aims to accurately predict the flexural strength (FS) of glass fiber reinforced concrete (GFRC) using advanced machine learning (ML) techniques. A novel algorithm, tree structured parzen estimator based extreme gradient boosting (TPE-XGB), is proposed by integrating Bayesian optimization (TPE) for automated hyperparameter tuning with the predictive strength of XGB. In addition to TPE-XGB, other ML algorithms including bagging regressor (BR), gene expression programming (GEP), and multi expression programming (MEP) are also employed for comparison. A comprehensive dataset consisting of 227 experimental instances of GFRC flexural strength was compiled from 33 internationally published studies. The models were trained and evaluated using statistical error metrics, k fold cross validation, scatter plots, and residual analysis. Results showed that all models performed reliably, with TPE-XGB achieving the highest prediction accuracy (testing R 2 value of 0.972). In contrast, GEP and MEP, described as grey box models that produce interpretable mathematical expressions, offered empirical equations for FS prediction which enhanced transparency. To further address the non-transparent nature of black box models like TPE-XGB, explainable machine learning (XML) techniques were applied. These included SHAP (Shapley Additive Explanations), Individual Conditional Expectation (ICE), and Partial Dependence Plots (PDP). The analysis revealed that water to cement ratio, quantities of fine and coarse aggregates, and glass fiber content were the most influential variables affecting the flexural performance of GFRC. Finally, a graphical interface is proposed to demonstrate the practical usability of the developed models. This study contributes both accurate prediction tools and interpretable insights, supporting improved and informed design practices in concrete technology.

Adsorption of 4-bromophenol from simulated wastewater using magnetic carbon-based composites: Kinetics, equilibrium, thermodynamics, and density functional theory analysis - Beatris L. Mello; Pascal S. Thue; Ali Hamid; Muhammad Usama; Fernando Machado Machado; Moaaz K. Seliem; Younes Dehmani; Glaydson S. dos Reis; Mohamed Abdel Salam; Hammad Khan; Luis F.O. Silva; Eder C. Lima (Journal of Water Process Engineering, 2025)

Comment on: “Genome-wide association study of direct oral anticoagulants and their relation to bleeding” - Muhammad Umar Farooque Khoso; Muhammad Hammad Chola; Muhammad Hasan (European Journal of Clinical Pharmacology, 2025)

Impact of Climatic Variables on Fruit Bearing Behavior and Disease Incidence in Commercial Mango Cultivars in a Semi-arid Region - Hafiz Mohkum Hammad; Talal Tariq; Shafqat Saeed; Muhammad Tariq Malik; Hafiz Faiq Siddique; Rashid Jawad; Shah Fahad; Ifrah Kanwal; Aitazaz A. Farooque (Applied Fruit Science, 2025)

Macroalgae Polysaccharides Enhance Brain Health by Mitigating Scopolamine-induced Oxidative Stress and Inflammation Via Nrf-2/TLR4/NF-kB Pathways - Zahir Shah; Arshad Iqbal; Syed Lal Badshah; Mushtaq Ahmad Mir; Saima Sohni; Hammad Ullah; Shahid Ali Shah; Nasreena Bashir; Muhammad Ayaz; Maria Daglia (Journal of Neuroimmune Pharmacology, 2025)

The Indonesian Throughflow regulated Australian summer monsoon across the Mid-Brunhes Event - Muhammad Sarim; Jian Xu; Xin Cheng; Peng Zhang; Junwen Wang; Maqsood Ur Rahman; Tayyab Jan; Hammad Ahmad (Quaternary Science Reviews, 2025)

Multiple integrated computational approach to analyse wound healing potential of Symplocos racemosa bark as Matrix metalloproteinase inhibitors - Hafiz Abdul Rafey; Adnan Amin; Samir Anis Ross; Mohamed El-Shazly; Muhammad Ammar Zahid; Shah Iram Niaz; Fakhar Ul Mahmood; Hammad Ullah (Natural Product Research, 2025)

Importance of an Oncology Interest Group in Medical School: Experience from a Developing Country - Hammad Atif Irshad; Abdul Rehman; Muhammad Ali Akbar Khan; Dahir Ashfaq; Munira Moosajee (Journal of Cancer Education, 2025)

A host availability-driven model for predicting the distribution of Red Palm Weevil in China - Umer Hayat; Muhammad Hammad Ahmad; Waqar Sattar; Ziying Zhu (Crop Protection, 2025)

Investigating the Role of Gibberellic Acid in Fruit Drop Mitigation and Fruit Quality Improvement in Date Palm Cultivars - Hammad Hussain; Yue Yu; Abdul Haseeb Ahmed; Faisal Hayat; Muhammad Awais; Abdullah Ma’Arij; Guo Wei; Rashad Qadri (Applied Fruit Science, 2025)

Performance and data acquisition from low-cost air quality sensors: a comprehensive review - Mubashir Ali Siddiqui; Mirza Hammad Baig; Muhammad Uzair Yousuf (Air Quality, Atmosphere & Health, 2025)

Valorization of recycled steel wires from end-of-life tires as an alternative fiber reinforcement in geopolymer concrete to foster circularity: a review - Muhammad Umer; Junaid Ahmad; Hammad Anis Khan; Rao Arsalan Khushnood (European Journal of Environmental and Civil Engineering, 2025)

Effect of resveratrol on post-thaw motility, kinematics, structural parameters and antioxidant/oxidant status of Kamori buck spermatozoa - Tarique Hussain; Muhammad Hammad Fayyaz; Amjad Hameed; Syed Murtaz Hassan Andrabi; Rehana Kausar; Yasin Mubashir; Iqra Batool; Muhammad Shahzad; Ali Dogan Omur (Cryobiology, 2025)

Effects of dietary organic selenium, vitamin C, and vitamin E supplementation on growth performance, serum biochemistry, and antioxidant status in juvenile Hypophthalmichthys molitrix - Hairui Yu; Maida Mushtaq; Saira Razzaq; Umar Ali; Muhammad Khan; Abdur Rahman; Guobo Quan; Mehroze Fatima; Saima Naveed; Muhammad Hammad Zafar; Muhammad Aziz ur Rahman (Frontiers in Marine Science, 2025)
The study aimed to evaluate the effects of dietary supplementation of selenium (Se), vitamin C, and vitamin E on growth performance, meat quality, and antioxidant status in Hypophthalmichthys molitrix juveniles. A total of 480 juveniles (mean weight: 20 ± 0.29 g) were randomly assigned to 24 aquaria (20 fish per 100 L), which were allocated to eight dietary treatments (three aquaria per treatment) following a completely randomized design. The dietary treatments included: (1) a basal diet without supplementation (Control), (2) selenium supplementation (S), (3) vitamin C supplementation (C), (4) vitamin E supplementation (E), (5) selenium and vitamin C supplementation (SC), (6) selenium and vitamin E supplementation (SE), (7) vitamin C and vitamin E supplementation (EC), and (8) selenium, vitamin C, and vitamin E supplementation (SCE). The supplementation levels were 0.9 mg/kg Se, 300 mg/kg vitamin C, and 100 mg/kg vitamin E, respectively. After a one-week acclimatization period, a 10-week growth trial was conducted. Fish fed the SCE diet exhibited significantly higher (p< 0.05) final weight gain, body length gain, body weight gain percentage, and specific growth rates compared to other treatments. Selenium concentrations in the kidney, liver, pancreas, and muscle were significantly higher (p< 0.05) in the SCE, SC, SE, and EC groups compared to the Control and single-supplement groups. Hematological parameters, including WBC, RBC, HGB, HCT, and MCHC, were significantly higher (p< 0.05) in the SCE group compared to all other groups. Similarly, serum activities of ALT, AST, and ALP were significantly lower (p< 0.05) in the SCE group than in other treatments, while blood glucose levels were unaffected (p > 0.05) by dietary treatments. Antioxidant enzyme activities, including superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx), were significantly enhanced (p< 0.05) in the whole body and muscle tissues of fish receiving Se, vitamin C, and E supplementation. Thiobarbituric acid reactive substances (TBARS) levels in muscle and serum were significantly higher (p< 0.05) in the Control group compared to all supplemented groups. The proximate composition of meat, including dry matter, fat, ash, and protein contents, was not significantly affected (p > 0.05) by the dietary treatments. In conclusion, dietary supplementation of selenium, vitamin C, and vitamin E significantly improved growth performance, selenium deposition in tissues, and antioxidant status of Hypophthalmichthys molitrix juveniles, without adversely affecting meat chemical composition.

From pollutant to purifier: Leveraging plastic waste-derived activated carbon for sustainable water remediation solutions - Hammad Khan; Muhammad Usama; Mohammad Ilyas Khan; Fazal Wahab; Izhar Ahmad; Ali Hamid; Sajjad Hussain; Arslan Maqbool (Journal of Environmental Management, 2025)

Bio-catalytic activity of novel poly(ethylene glycol) methacrylate hybridized silver nanomaterials - Natasha Anwar; Mohib Shah; Saad Haroon Anwar; Muhammad Ishaq Ali Shah; Amir Zada; Hammad Ahmad Jan; Abeer Hashem; Graciela Dolores Avila-Quezada; Elsayed Fathi Abd-Allah (South African Journal of Botany, 2025)

Assessing the Effectiveness of Audio-Visual vs. Visual Neurofeedback for Attention Enhancement: A Pilot Study with Neurological, Behavioural, and Neuropsychological Measures - Osama Ejaz; Muhammad Abul Hasan; Faryal Raees; Maham Hammad; Saad Ahmed Qazi (Brain Topography, 2025)

Retraction Note: Protective effect of myricetin on nonylphenol-induced testicular toxicity: biochemical, steroidogenic, hormonal, spermatogenic, and histological-based evidences - Muhammad Umar Ijaz; Haseeb Anwar; Shabnoor Iqbal; Hammad Ismail; Asma Ashraf; Shama Mustafa; Abdul Samad (Environmental Science and Pollution Research, 2024)

Unveiling the biosorption performance of silk fibroin fiber for Pb(II) and Cr(VI) removal: Machine learning and DFT analysis - Muhammad Usman Farooq; Hammad Khan; Muhammad Arshad; Muhammad Usama; Mohammad Ilyas Khan; Sajjad Hussain; Ali Hamid (Journal of Water Process Engineering, 2024)

Utilizing Cinnamomum verum (a culinary spice), as a functional food ingredient ameliorating hypercholesterolemia: In-vivo, in-vitro, and in-silico multi-model analysis - Mahnoor Bano; Muhammad Khurram Waqas; Talha Ali Chohan; Fakhra Batool; Aamir Mushtaq; Yahya I. Asiri; Mohd. Zaheen Hassan; Md Ali Mujtaba; Md. Khalid Anwer; Muhammad Irfan Sidique; Ayesha Riaz; Umair Khurshid; et al. (Food Bioscience, 2024)

The interplay of PTEN and AKT nexus in breast cancer: a molecular perspective - Anum Kamal; Ali Raza Awan; Masood Rabbani; Hammad Raza Sheikh; Muhammad Tayyab; Sehrish Firyal; Imran H. Khan; Muhammad Wasim (Molecular Biology Reports, 2024)

Evaluating the biological activity of rolB-transgenic Nicotiana tabacum plants using phytochemical and pharmacological approaches - Afshan Anwar; Shabana Haneef; Hammad Ismail; Muhammad Zeeshan Bhatti; Nazif Ullah; Iram Murtaza; Bushra Mirza (Plant Biosystems, 2024)

Nutritional and medicinal plants as potential sources of enzyme inhibitors toward the bioactive functional foods: an updated review - Hammad Saleem; Anam Yaqub; Rabiya Rafique; Tahir Ali Chohan; Durr-e-Shahwar Malik; Muhammad Imran Tousif; Umair Khurshid; Nafees Ahemad; Ramasamy Ramasubburayan; Kannan RR Rengasamy (Critical Reviews in Food Science and Nutrition, 2024)

Adsorptive removal of cationic dyes from wastewater using a novel sodium alginate-based iron oxide nanocomposite hydrogel: DFT and advanced statistical physics modelling - Muhammad Umar; Muhammad Usman Farooq; Muhammad Arshad; Muhammad Usama; Feryal Akbal; Sajjad Hussain; Hammad Khan (Process Safety and Environmental Protection, 2024)

Depositional architecture of early rift non-marine systems and implications for reservoir development: Oligocene to Miocene Al Wajh Formation, Midyan Basin of Red Sea, Saudi Arabia - Muhammad Naveed Butt; Arif Hussain; Muhammad Hammad Malik; Abduljamiu O. Amao; Ardiansyah Koeshidayatullah; Cornel Olariu; Abdulwahab Muhammad Bello; Khalid Al-Ramadan (Marine and Petroleum Geology, 2024)

Field validation of NDVI to identify crop phenological signatures - Muhammad Tousif Bhatti; Hammad Gilani; Muhammad Ashraf; Muhammad Shahid Iqbal; Sarfraz Munir (Precision Agriculture, 2024)
Purpose and Methods Crop identification using remotely sensed imagery provides useful information to make management decisions about land use and crop health. This research used phonecams to acquire the Normalized Difference Vegetation Index (NDVI) of various crops for three crop seasons. NDVI time series from Sentinel (L121-L192) images was also acquired using Google Earth Engine (GEE) for the same period. The resolution of satellite data is low therefore gap filling and smoothening filters were applied to the time series data. The comparison of data from satellite images and phenocam provides useful insight into crop phenology. The results show that NDVI is generally underestimated when compared to phenocam data. The Savitzky-Golay (SG) and some other gap filling and smoothening methods are applied to NDVI time series based on satellite images. The smoothened NDVI curves are statistically compared with daily NDVI series based on phenocam images as a reference. Results The SG method has performed better than other methods like moving average. Furthermore, polynomial order has been found to be the most sensitive parameter in applying SG filter in GEE. Sentinel (L121-L192) image was used to identify wheat during the year 2022–2023 in Sargodha district where experimental fields were located. The Random Forest Machine Leaning algorithm was used in GEE as a classifier. Conclusion The classification accuracy has been found 97% using this algorithm which suggests its usefulness in applying to other areas with similar agro-climatic characteristics.

Genetic testing perspectives in Pakistani population: a survey on knowledge, attitudes, awareness, and concerns - Mohammad Uzair; Rida Fatima; Shafia Rafiq; Maimoona Jabeen; Hammad Qaiser; Muhammad Arshad; Shahid Bashir (Journal of Community Genetics, 2024)

Design and Evaluation of Inorganic/Organic Hybrid Bio-composite for Site-Specific Oral Delivery of Darifenacin - Wafa Ishaq; Attia Afzal; Muhammad Farooq; Muhammad Sarfraz; Sherjeel Adnan; Hammad Ahmed; Muhammad Waqas; Zainab Safdar (AAPS PharmSciTech, 2024)
Benign hyperplasia (BHP) is a common disorder that affects men over the age of 60 years. Transurethral resection of the prostate (TURP) is the gold standard for operative treatment, but a range of drugs are also available to improve quality of life and to reduce BHP-associated urinary tract infections and complications. Darifenacin, an anti-muscarinic agent, has been found effective for relieving symptoms of overactive bladder associated with BHP, but the drug has poor solubility and bioavailability, which are major challenges in product development. An inorganic/organic bio-composite with gastric pH-resistant property was synthesized for the targeted oral delivery of Darifenacin to the lower gastrointestinal tract (GIT). This development was accomplished through co-precipitation of calcium carbonate in quince seed-based mucilage. The FTIR, XRD, DSC, and TGA results showed good drug-polymer compatibility, and the SEM images showed calcite formation in the quince hydrogel system. After 72 h, the drug release of 34% and 75% were observed in acidic (0.1N HCl) and 6.8 pH phosphate buffer, respectively. A restricted/less drug was permeated through gastric membrane (21.8%) as compared to permeation through intestinal membrane (65%.) The developed composite showed significant reduction in testosterone-induced prostatic hyperplasia (2.39 ± 0.12***) as compared to untreated diseased animal group. No sign of organ toxicity was observed against all the developed composites. In this study, we developed an inorganic–organic composite system that is highly biocompatible and effective for targeting the lower GIT, thereby avoiding the first-pass metabolism of darifenacin. Graphical Abstract

The Cambrian sedimentology and reservoir properties of the hybrid Abbottabad Formation in the Kotli area, Sub-Himalaya, Pakistan: insights into the Proto-Tethys paleoenvironment - Syed Kamran Ali; Rafiq Ahmad Lashari; Ali Ghulam Sahito; George Kontakiotis; Hammad Tariq Janjuhah; Muhammad Saleem Mughal; Tariq Mahmood (Carbonates and Evaporites, 2024)

Light-driven C1 Chemical Conversion with LDH-based Nanomaterials - Zixi Liu; Muhammad Altaf Nazir; Muhammad Altaf; Hammad Majeed; Zeinhom M. El-Bahy; Mohamed H. Helal; Abdul Rauf; Sami Ullah; Tayyaba Najam; Syed Shoaib Ahmad Shah; Aziz ur Rehman (Applied Clay Science, 2024)

Diagenetic variability in Tertiary, syn-rift mixed siliciclastic‑carbonate depositional system (Lower Musayr Formation), Red Sea, Saudi Arabia - Arif Hussain; Abdulwahab Bello; Muhammad Naveed Butt; Muhammad Hammad Malik; Ardiansyah Koeshidayatullah; Abduljamiu Amao; Cornel Olariu; Khalid Al-Ramadan (Sedimentary Geology, 2024)

Integrated AI-driven optimization of Fenton process for the treatment of antibiotic sulfamethoxazole: Insights into mechanistic approach - Saima Gul; Sajjad Hussain; Hammad Khan; Muhammad Arshad; Javaid Rabbani Khan; Artur de Jesus Motheo (Chemosphere, 2024)

Soil Organic Carbon and Nitrogen Mineralization Potential of Manures Regulated by Soil Microbial Activities in Contrasting Soil Textures - Waqar Ahmed; Muhammad Nadeem Ashraf; Muhammad Sanaullah; Muhammad Aamir Maqsood; Muhammad Ahmed Waqas; Shafeeq Ur Rahman; Saddam Hussain; Hammad Raza Ahmad; Adnan Mustafa; Xu Minggang (Journal of Soil Science and Plant Nutrition, 2024)

Assessing Asiatic black bear (Ursus thibetanus) temporal overlap and co-occurrence with sympatric species in the temperate zone of the Hindu Raj Mountain range - Faizan Ahmad; Muhammad Rehan; Eve Bohnett; Ammar Hassan; Sami Ullah; Shah Zeb; Hammad Ali Mian; Muhammad Kabir (European Journal of Wildlife Research, 2024)

Integrated sedimentary and diagenetic constraints for delineating the reservoir potential of Jurassic carbonate sequences in the autochthonous Samana Suk Formation, Attock-Cherat Nizampur Area, Pakistan - Muhammad Ibrar; Sajjad Khan; Mehboob Ur Rashid; George Kontakiotis; Ihtisham Islam; Hammad Tariq Janjuhah; Assimina Antonarakou (Carbonates and Evaporites, 2024)

IoT-based agriculture management techniques for sustainable farming: A comprehensive review - Hammad Shahab; Muhammad Iqbal; Ahmed Sohaib; Farid Ullah Khan; Mohsin Waqas (Computers and Electronics in Agriculture, 2024)

High strength rubberized porous concrete for sustainable pavements: Engineering properties and life cycle assessment - Musa Ajmal Khan; Junaid Ahmad; Hammad Anis Khan; Muhammad Umer (Journal of Cleaner Production, 2024)

Integrating DFT and machine learning for the design and optimization of sodium alginate-based hydrogel adsorbents: Efficient removal of pollutants from wastewater - Muhammad Umar; Hammad Khan; Sajjad Hussain; Muhammad Arshad; Hyeok Choi; Eder C. Lima (Environmental Research, 2024)

Multi-Elemental Chemostratigraphy, Sequence Development, Depositional History, and Environmental Importance of Early Eocene Red Beds (Kuldana Formation) in NW Himalayas, Pakistan - Amir Shahzad; George Kontakiotis; Thierry Adatte; Khawaja Shoaib Ahmed; Muhammad Tayyib Riaz; Hammad Tariq Janjuhah; Evangelia Besiou (Journal of Earth Science, 2024)

Retraction Note: Environmental factors affecting the frequency of road traffic accidents: a case study of sub-urban area of Pakistan - Hafiz Mohkum Hammad; Muhammad Ashraf; Farhat Abbas; Hafiz Faiq Bakhat; Saeed A. Qaisrani; Muhammad Mubeen; Shah Fahad; Muhammad Awais (Environmental Science and Pollution Research, 2024)

Retraction Note: Trends of electronic waste pollution and its impact on the global environment and ecosystem - Rida Akram; Natasha; Shah Fahad; Muhammad Zaffar Hashmi; Abdul Wahid; Muhammad Adnan; Muhammad Mubeen; Naeem Khan; Muhammad Ishaq Asif Rehmani; Muhammadd Awais; Mazhar Abbas; Khurram Shahzad; et al. (Environmental Science and Pollution Research, 2024)

Socio-environmental factors and solar housing system adoption: moderating effect of attitude - Ahsen Maqsoom; Muhammad Hammad; Muhammad Umer; Wesam Salah Alaloul; Hassan Ashraf; Muhammad Ali Musarat; Tahira Nazir (Innovative Infrastructure Solutions, 2024)

Synthesis and characterizations of conocarpus- and azadirachta-derived activated carbons as wastewater recycling material - Murtuza Mehdi; Mirza Hammad Baig; Masood Ahmad; Kamran Ali; Muhammad Mohib; Ali Farooqi; Mohammad Affan; Muhammad Mazin (Environmental Monitoring and Assessment, 2024)

Effect of riboflavin on redox balance, osmolyte accumulation, methylglyoxal generation and nutrient acquisition in indian squash (Praecitrullus fistulosus L.) under chromium toxicity - Habiba Kanwal; Syed Hammad Raza; Shafaqat Ali; Muhammad Iqbal; Mudassir Iqbal Shad (Environmental Science and Pollution Research, 2024)

Cerium oxide nanoparticles improve the post-thaw quality and in-vivo fertility of Beetal buck spermatozoa - Mubashir Ali Khalique; Syed Murtaza Hassan Andrabi; Khalid Abdul Majeed; Muhammad Shahbaz Yousaf; Nisar Ahmad; Sajid Khan Tahir; Muhammad Hammad Fayyaz; Muhammad Shafiq Haider; Syeda Sohaila Naz; Irfan Zia Qureshi; Sulaiman Sulaiman; Hafsa Zaneb; et al. (Theriogenology, 2024)

Unveiling the dynamic impact of energy generation on economic sustainability in Canada: A roadmap towards sustainable development - Mohammad Subhan; Muhammad Irfan; Xuen Pan; Gayas Ahmad; Mohd Hammad Naeem; M.N. Zamir (Journal of Cleaner Production, 2024)

Unleashing the dye adsorption potential of polyaminoimide homopolymer: DFT, statistical physics, site energy and pore size distribution analyses - Nabeel Hussain; Hammad Khan; Sajjad Hussain; Muhammad Arshad; Muhammad Umar; Fazal Wahab (Journal of Environmental Chemical Engineering, 2023)

Sustainable wastewater purification with crab shell-derived biochar: Advanced machine learning modeling & experimental analysis - Amina Bibi; Hammad Khan; Sajjad Hussain; Muhammad Arshad; Fazal Wahab; Muhammad Usama; Khurram Khan; Feryal Akbal (Bioresource Technology, 2023)

A decline in snow cover area of Passu and Ghulkin valleys between 1995 and 2022 - Imran Hussain; Mumtaz Ali; Sher Muhammad; Wajid Hassan; Salar Ali; Zakir Hussain; Syed Hammad Ali; Shaukat Ali; Muhammad Younis Khan (Journal of Mountain Science, 2023)

Selective capture of uranium and zirconium from strong HNO3 solution by ethenylphosphonic acid copolymerized polymer - Muhammad Hammad ul Haq; Xu Zhang; Fengqi Zhang; Alemtsehay Tesfay Reda; Dongxiang Zhang; Muhammad Zahid; Muhammad Khurram Tufail; Muhire Constantin; Noor Hasaan; Jinying Li; Xiyan Xu (Chemical Engineering Journal, 2023)

Multiple design and modelling approaches for the optimisation of carbon felt electro-Fenton treatment of dye laden wastewater - Hammad Khan; Sajjad Hussain; Muhammad Amad Ud Din; Muhammad Arshad; Fazal Wahab; Usman Hassan; Abad Khan (Chemosphere, 2023)

Evaluation of possible attenuative role of chrysoeriol against polyethylene microplastics instigated testicular damage: A biochemical, spermatogenic and histological study - Muhammad Umar Ijaz; Faria Saher; Nemra Aslam; Ali Hamza; Haseeb Anwar; Saad Alkahtani; Hammad Ahmad Khan; Mian Nadeem Riaz (Food and Chemical Toxicology, 2023)

Exploring the role of HaTIPs genes in enhancing drought tolerance in sunflower - Tania Safdar; Muhammad Hammad Nadeem Tahir; Zulfiqar Ali; Muhammad Habib ur Rahman (Molecular Biology Reports, 2023)

Cryopreservation protocol resolving the "temperature" challenges of long-distance transportation of Beetal buck (Capra hircus) sperm - Syed Aftab Hussain Shah; Muhammad Shafiq Haider; Hussain Ahmed; Muhammad Hammad Fayyaz; Syed Murtaza Hassan Andrabi (Small Ruminant Research, 2023)

Bio-fortification of Two Wheat Cultivars with Iron and Zinc Through Their Soil and Foliar Application in Salt-Factored Soil: Growth, Ionic, Physiological, and Biochemical Modifications - Tayyaba Naz; Muhammad Mazhar Iqbal; Shah Fahad; Javaid Akhtar; Muhammad Saqib; Saud Alamri; Manzer H. Siddiqui; Shah Saud; Jabar Zaman Khan Khattak; Shamsher Ali; Shah Hassan; Taufiq Nawaz; et al. (Journal of Plant Growth Regulation, 2023)

Green investment, institutional quality, and environmental performance: evidence from G-7 countries using panel NARDL approach - Jiguo Zhao; Saif ur Rahman; Sahar Afshan; Muhammad Sibt E. Ali; Hammad Ashfaq; Sadia Idrees (Environmental Science and Pollution Research, 2023)

Antioxidant effects of zinc-oxide nanoparticles on post-thaw quality and in vivo fertility of Beetal buck spermatozoa - Mubashir Ali Khalique; Habib Rehman; Syed Murtaza Hassan Andrabi; Khalid Abdul Majeed; Nisar Ahmad; Muhammad Hammad Fayyaz; Muhammad Shafiq Haider; Syeda Sohaila Naz; Irfan Zia Qureshi; Sulaiman Sulaiman (Small Ruminant Research, 2023)

Phytochemical, biological, and in-silico analysis of Colutea armata Hemsl. & Lace: A possible source of bioactive natural compounds - Ayisha Khalid; Samina Afzal; Farhan Abbas; Iftikhar Afzal; Muhammad Iqbal; Sarfraz Ahmad; Siddique Akber Ansari; Hamad M. Alkahtani; Tahir Ali Chohan; Umair Khurshid; Hammad Saleem; Carlos Leonardo Cespedes-Acuna (South African Journal of Botany, 2023)

Inclusiveness in Food Data Sets: Development of a Food Composition Dataset for South Asian Recipes With Focus on Pakistan - Muhammad Hammad Maqdoom; Syeda Areesha Najam; Shalin Ali; Sana Fatima; Alisha Momin; Abdul Samad; Humaira Jamshed (Journal of Nutrition Education and Behavior, 2023)

Modelling the ingress and charge enhanced deposition behaviour of radioactive aerosols in dwellings - Tashfeen Muhammad Hammad Ud Din; Miriam A. Byrne; James A. McGrath (Atmospheric Environment, 2023)

Sedimentological, Diagenetic, and Sequence Stratigraphic Controls on the Shallow to Marginal Marine Carbonates of the Middle Jurassic Samana Suk Formation, North Pakistan - Shazia Qamar; Mumtaz Muhammad Shah; Hammad Tariq Janjuhah; George Kontakiotis; Amir Shahzad; Evangelia Besiou (Journal of Marine Science and Engineering, 2023)
This study presents a thorough analysis of the sedimentology, diagenesis, and sequence stratigraphy of the Middle Jurassic Samana Suk Formation in the Hazara Basin of northern Pakistan. Focusing on two sections, namely Mera Rehmat and Por Miana, the research aims to unravel the complex geological processes within the formation. The examination of microfacies reveals nine distinct depositional textures, ranging from mudstone to wackestone, packstone, and grainstone, indicating various inner ramp environments such as open marine, lagoon, and coastal settings. Petrographic investigations shed light on diagenetic processes, including micritization, cementation, dissolution, compaction, neomorphism, and dolomitization. Six cementation types are identified, and the dolomitization patterns vary, providing insights into lagoonal environments and mudstone replacement. Sequence stratigraphic analysis uncovers intriguing patterns within the Samana Suk Formation. The high-stand system tract is characterized by mudstones, pelloidal grainstones, and dolomitized mudstones, indicating periods of high sea level. In contrast, the transgressive system tract displays ooidal grainstones, pelloidal packstones, and pel-bioclastic grainstones, representing transgression and inundation of previously exposed areas. A significant finding is the impact of diagenesis on reservoir quality parameters, specifically porosity, and permeability. Diagenetic processes, cementation types, and dolomitization patterns have significantly altered the pore network, highlighting the importance of considering diagenesis in assessing the Samana Suk Formation as a hydrocarbon reservoir. This research provides a comprehensive understanding of the sedimentology, diagenesis, and sequence stratigraphy of the Middle Jurassic Samana Suk Formation. The findings contribute to our knowledge of similar carbonate reservoirs globally, enhancing the exploration and development of hydrocarbon resources in comparable depositional environments.

Triladyl® improves the cryopreserved quality and in vivo fertilization potential of Beetal buck (Capra hircus) spermatozoa - Syed Aftab Hussain Shah; Muhammad Shafiq Haider; Hussain Ahmed; Muhammad Hammad Fayyaz; Syed Murtaza Hassan Andrabi (Small Ruminant Research, 2023)

A comprehensive review on the botany, traditional uses, phytochemistry, pharmacology and toxicity of Anagallis arvensis (L).: A wild edible medicinal food plant - Hammad Saleem; Umair Khurshid; Muhammad Imran Tousif; Sirajudheen Anwar; Nasser A. Awadh Ali; Mohamad Fawzi Mahomoodally; Nafees Ahemad (Food Bioscience, 2023)

Fullerenol [60] Nano-cages for Protection of Crops Against Oxidative Stress: A Critical Review - Fahad Shafiq; Muhammad Iqbal; Syed Hammad Raza; Nudrat Aisha Akram; Muhammad Ashraf (Journal of Plant Growth Regulation, 2023)

Sedimentological and Petrographical Characterization of the Cambrian Abbottabad Formation in Kamsar Section, Muzaffarabad Area: Implications for Proto-Tethys Ocean Evolution - Syed Kamran Ali; Rafiq Ahmad Lashari; Ali Ghulam Sahito; George Kontakiotis; Hammad Tariq Janjuhah; Muhammad Saleem Mughal; Ahmer Bilal; Tariq Mehmood; Khawaja Umair Majeed (Journal of Marine Science and Engineering, 2023)
The current sedimentological and petrographical research of the Abbottabad Formation has been carried out in order to understand the formation and evolution of the Proto-Tethys Ocean during the Cambrian on the northern margin of the Indian Plate. The Muzaffarabad region is located east of the Upper Indus Basin and the southern part of the Hazara Kashmir Syntaxis. The geological history of the region varies from the Precambrian to the recent period. The Cambrian Abbottabad Formation is well exposed along the Hazara Kashmir Syntaxis at the core of the 500-m-thick Muzaffarabad anticline. The Abbottabad Formation is an unconformity-bounded allo-stratigraphic unit. It has an unconformable lower contact with the Late Precambrian Dogra Formation and an unconformable upper contact with the Paleocene Hangu Formation. The Abbottabad Formation has been divided into four lithofacies, from bottom to top, namely, thinly interbedded dolomite and shale, cherty-stromatolitic dolomite, oxidized limonitic-brecciated zone, and quartzite, with significant lithological changes. Petrographic studies revealed four types of dolomites: fine crystalline dolomite (Dol. I), dolomitic cryptocrystalline chert (Dol. II), algal mat-stromatolitic dolomite (Dol. III), and intraclastic-dolo-grain stone (Dol. IV). The mineral composition of dolostone was analyzed using X-ray diffraction (XRD) and found to be consistent with previous petrographic studies. The dolomite mineral content decreased from base to top, while chert increased towards the top. Elemental weight percentages through energy dispersive X-ray (EDX) analysis show different elements constitute the minerals found in the dolostone, as confirmed by petrographic and XRD analysis. Using outcrop data, facies information, and geochemical data, a modified depositional model of the Abbottabad Formation was developed. During the Early Cambrian period, the formation was deposited in a shallow subtidal to supratidal setting of the Proto-Tethys Ocean. The top of this deposit marks the Cambrian–Paleocene boundary. Because of the progressively coarsening outcrop sequences, this formation seems to be at the very top of the Proto-Tethys Ocean’s shallow marine system.

Impacts of COVID-19 pandemic on environment, society, and food security - Hafiz Mohkum Hammad; Hafiz Muhammad Fasihuddin Nauman; Farhat Abbas; Rashid Jawad; Wajid Farhad; Muhammad Shahid; Hafiz Faiq Bakhat; Aitazaz A. Farooque; Muhammad Mubeen; Shah Fahad; Artemi Cerda (Environmental Science and Pollution Research, 2023)

Evaluating adoption of climate smart agricultural practices among farmers in the Fujian Province, China - Rao Sabir Sattar; Muhammad Sajid Mehmood; Muhammad Hammad Raza; V. P. I. S. Wijeratne; Babar Shahbaz (Environmental Science and Pollution Research, 2023)

Zeolite amendment reduces lead accumulation and improves growth and yield in tomato plants irrigated with sewage water - Rashid Jawad; Aamir Nawaz; Shaghef Ejaz; Sajid Ali; Muhammad Shahzad Saleem; Hafiz Mohkum Hammad (Environmental Science and Pollution Research, 2023)

Novel modeling and optimization framework for Navy Blue adsorption onto eco-friendly magnetic geopolymer composite - Hammad Khan; Sajjad Hussain; Rehman Zahoor; Muhammad Arshad; Muhammad Umar; Mohsin Ali Marwat; Adnan Khan; Javaid Rabbani Khan; Muhammad Abdul Haleem (Environmental Research, 2023)

Economic feasibility of solar-powered reverse osmosis water desalination: a comparative systemic review - Abderrahim Maftouh; Omkaltoume El Fatni; Siham Bouzekri; Fateme Rajabi; Mika Sillanpää; Muhammad Hammad Butt (Environmental Science and Pollution Research, 2023)

Sedimentology and Diagenesis of the Early–Middle Eocene Carbonate Deposits of the Ceno-Tethys Ocean - Ahmer Bilal; Renchao Yang; Muhammad Saleem Mughal; Hammad Tariq Janjuhah; Muhammad Zaheer; George Kontakiotis (Journal of Marine Science and Engineering, 2022)
An integrated study based on field observation, petrography, and scanning electron microscopy (SEM) on the Early–Middle Eocene carbonate rocks has been carried out, which were deposited in the Ceno-Tethys Ocean. The study area of the Yadgaar Section lies on the eastern margin of the Upper Indus Basin, Pakistan. The Early–Middle Eocene Margalla Hill Limestone and Chorgali Formation act as reservoir rocks in other parts of the basin and are also present in the Yadgaar Section. The lack of comprehensive study in this area makes these reservoir rocks highly attractive for sedimentological evaluations and future exploration of hydrocarbons. The Early–Middle Eocene carbonate rocks are divided into nine microfacies: dolomicritic foraminiferal mudstone–wackestone microfacies (EMI); green algae dominated, mixed foraminiferal wackestone–packstone microfacies (EMII); ostracod, green algae and gypsum dominating mudstone–wackestone microfacies (EMIII); algae and mixed foraminiferal wackestone–packstone microfacies (EMIV); Nummulites dominating mudstone–wackestone microfacies (EMV); algal limestone mudstone microfacies (EMVI); Assilina bed wackestone–packstone microfacies (EMVII); micritized larger benthic foraminiferal wackestone–packstone microfacies (EMVIII); and algal limestone, mudstone microfacies (EMIX). The transgressive-regressive environment in the Ceno-Tethys Ocean leads to the deposition of these microfacies in the platform interior, open marine platform, platform edge, platform margin reef, toe of the slope apron, arid–humid platform interior, platform edge, open marine platform interior, and restricted marine platform interior, respectively. Initial post-depositional diagenetic stages are identified from the base to the top of the strata by their respective cement types, i.e., the base–lower middle part of the strata demonstrates an eogenetic sub-stage with the appearance of drusy cement, the middle section indicates a mesogenetic sub-stage by the appearance of blocky cement, while the top portion again reveals an eogenetic sub-stage of diagenesis by the presence of drusy and blocky types of cement. The ascending–descending hierarchy of cement generations is directly proportional to the grade of diagenesis from the base to the top of the carbonate strata. Variable diagenetic effects on the various microfacies also increase the secondary porosity range and enhance the reservoir characteristics of the Formations. The presence of foraminifera microfossils determined that these carbonate formations date from the Early–Middle Eocene.

Correction: Fazal et al. Geochemical Analysis of Cretaceous Shales from the Hazara Basin, Pakistan: Provenance Signatures and Paleo-Weathering Conditions. J. Mar. Sci. Eng. 2022, 10, 800 - Abdul Ghaffar Fazal; Muhammad Umar; Faisal Shah; Muhammad Armaghan Faisal Miraj; Hammad Tariq Janjuhah; George Kontakiotis; Abdul Khaliq Jan (Journal of Marine Science and Engineering, 2022)
In the original publication [...]

Environmental factors and its influence on human health in BRICS: implications for human development - Wenxin Wang; Muhammad Hafeez; Hong Jiang; Waseem Ahmad; Hammad Badar; Raufhon Salahodjaev (Environmental Science and Pollution Research, 2022)

Occurrence of Microplastics and Heavy Metals in Aquatic and Agroecosystem: A Case Study - Tanveer Ahmad; Muhammad Amjad; Qumer Iqbal; Asmat Batool; Anam Noor; Muhammad Jafir; Hammad Hussain; Muhammad Irfan (Bulletin of Environmental Contamination and Toxicology, 2022)

Leaf rolling dynamics for atmospheric moisture harvesting in wheat plant as an adaptation to arid environments - Sabah Merrium; Zulfiqar Ali; Muhammad Hammad Nadeem Tahir; Muhammad Habib-ur-Rahman; Sadia Hakeem (Environmental Science and Pollution Research, 2022)
Plant species surviving in the arid regions have developed novel leaf features to harvest atmospheric water. Before the collected water evaporates, it is absorbed and transported for storage within the tissues and move toward the root zone through the unique chemistry of leaf structures. Deep insights into such features reveal that similarities can be found in the wheat plant. Therefore, this study aimed to evaluate the leaf rolling dynamics among wheat genotypes and their relationships with moisture harvesting and its movement on the leaf surface. For this purpose, genotypes were characterized for leaf rolling at three distinct growth stages (tillering, booting, and spike emergence). The contact angle of leaf surface dynamics (adaxial and abaxial), water budget, and morphophysiological traits of genotypes were measured. The results indicate that leaf rolling varies from inward to twisting type among genotypes and positively affected the water use efficiency and soil moisture difference at all growth stages under normal and drought conditions. Results of wetting property (hydrophilic < 90°) of the leaf surface were positively associated with the atmospheric water collection (4–7 ml). The lower values of contact angle hysteresis (12–19°) also support this mechanism. Thus, genotypes with leaf rolling dynamics (inward rolled and twisted) and surface wettability is an efficient fog harvesting system in wheat for interception and utilization of fog water in drought-prone areas. These results can be exploited to develop self-irrigated and drought-tolerant crops.

Assessment of land use/land cover changes and its effect on land surface temperature using remote sensing techniques in Southern Punjab, Pakistan - Sajjad Hussain; Muhammad Mubeen; Ashfaq Ahmad; Hamid Majeed; Saeed Ahmad Qaisrani; Hafiz Mohkum Hammad; Muhammad Amjad; Iftikhar Ahmad; Shah Fahad; Naveed Ahmad; Wajid Nasim (Environmental Science and Pollution Research, 2022)

Geochemical Analysis of Cretaceous Shales from the Hazara Basin, Pakistan: Provenance Signatures and Paleo-Weathering Conditions - Abdul Fazal; Muhammad Umar; Faisal Shah; Muhammad Miraj; Hammad Janjuhah; George Kontakiotis; Abdul Jan (Journal of Marine Science and Engineering, 2022)
The geochemical investigation of shales from the Early to Middle Cretaceous Chichali Formation in the Hazara Basin was conducted to determine the origin, tectonic setting and evolution, paleo-weathering conditions, and paleo-oceanographic reconstruction. The research included a comprehensive field survey, sample collection, and analysis of a variety of main, trace, and rare-earth elements using an X-ray fluorescence spectrometer (XRF). Bivariate plots and ternary diagrams were used to determine the provenance, tectonic setting, and paleo-weathering conditions that existed during the development of the Chichali Formation in the Hazara Basin. The values of Ba/Sc, Ba/Co, Th/Sc, Cr/Th, Cr/Zr, Th/Co, Th/Cr, Sc/Th, bivariate plots of Al2O3 vs. TiO2, TiO2 vs. Zr, TiO2 vs. Ni, Df1–Df2, Zr vs. Nb, and La/Sc vs. Th/Co, and ternary diagram of K2O–Fe2O3–Al2O3 were used to illustrate the passive continental margin setting of Chichali Formation shales. The detailed chemical analysis also provides an understanding of the marine geochemical cycle, which reflects the origin of these sediments. The average K2O/Al2O3 value is less than 0.4, indicating that the shale contains clay minerals. The Chichali Formation’s Chemical Index of Alteration (mean = 71) and Index of Compositional Variation (mean = 1.12) values show a modest degree of chemical weathering in the source locations. From an environmental standpoint, the Chichali Formation is richer in toxic elements such as Ba, Zn, Ni, Cr, and Cu, which may be damaging to agricultural soils and drinking water when present in excess. These metals are incorporated into the formation during the weathering process.

Interactive effect of amino acids balanced at ideal lysine ratio and exogenous protease supplemented to low CP diet on growth performance, carcass traits, gut morphology, and serum metabolites in broiler chicken - Muhammad Adeel Maqsood; Ehsaan Ullah Khan; Shafqat Nawaz Qaisrani; Muhammad Afzal Rashid; Muhammad Shabir Shaheen; Azhar Nazir; Hammad Talib; Sohail Ahmad (Tropical Animal Health and Production, 2022)

Pretreatment with Chitosan Arbitrates Physiological Processes and Antioxidant Defense System to Increase Drought Tolerance in Alfalfa (Medicago sativa L.) - Ghulam Mustafa; Muhammad Asif Shehzad; M. Hammad Nadeem Tahir; Fahim Nawaz; Gulzar Akhtar; Muhammad Asaad Bashir; Abdul Ghaffar (Journal of Soil Science and Plant Nutrition, 2022)

Exploring the potential effect of Achnatherum splendens L.–derived biochar treated with phosphoric acid on bioavailability of cadmium and wheat growth in contaminated soil - Muhammad Irfan; Khadim Dawar; Shah Fahad; Imran Mehmood; Saud Alamri; Manzer H. Siddiqui; Shah Saud; Jabar Zaman Khan Khattak; Shamsher Ali; Shah Hassan; Taufiq Nawaz; Hafiz Mohkum Hammad; et al. (Environmental Science and Pollution Research, 2022)

Developing monthly hydrometeorological timeseries forecasts to reservoir operation in a transboundary river catchment - Hammad-ur-Rehman; Ijaz Ahmad; Faraz-ul-Haq; Muhammad Waseem; Jinxin Zhang (Theoretical and Applied Climatology, 2022)

Genotypic Differences Among the Rice Genotypes to Arsenic Stress Cultivated Under Two Water Regimes: With an Inference to Human Health - Hafiz Faiq Bakhat; Sidra Arshad; Natasha; Sunaina Abbas; Ghulam Mustafa Shah; Shah Fahad; Hafiz Mohkum Hammad; Muhammad Sajjad; Muhammad Ashfaq; Muhammad Shahid (Journal of Plant Growth Regulation, 2022)

Depositional Sedimentary Facies, Stratigraphic Control, Paleoecological Constraints, and Paleogeographic Reconstruction of Late Permian Chhidru Formation (Western Salt Range, Pakistan) - Syed Kamran Ali; Hammad Tariq Janjuhah; Syed Muzyan Shahzad; George Kontakiotis; Muhammad Hussain Saleem; Usman Khan; Stergios D. Zarkogiannis; Panayota Makri; Assimina Antonarakou (Journal of Marine Science and Engineering, 2021)
The Upper Indus Basin, in Pakistan’s western Salt Range, is home to the Zaluch Gorge. The sedimentary rocks found in this Gorge, belonging to the Chhidru Formation, were studied in terms of sedimentology and stratigraphy, and provide new insights into the basin paleogeographic evolution from the Precambrian to the Jurassic period. Facies analysis in the Chhidru Formation deposits allowed the recognition of three lithofacies (the limestone facies—CF1, the limestone with clay interbeds facies—CF2, and the sandy limestone facies—CF3) with five microfacies types (mudstone biomicrite—MF-1, wackestone-biomicrite—MF-2, wackestone-biosparite—MF-3, pack-stone-biomicrite—MF-4, and packstone-biosparite—MF-5), as well as their depositional characteristics. The identified carbonate and siliciclastic formations display various facies in a shallow marine environment, with different lithologies, sedimentary features, and energy conditions. It is thought that the depositional characteristics of these microfacies are closer to those of the middle to outer shelf. Because of the progressively coarsening outcrop sequence, this formation seems to be at the very top of the high stand system tract (HST). A modified dynamic depositional model of the Chhidru Formation is further built using outcrop data, facies information, and stratigraphy. According to this concept, the formation was deposited in the middle to inner shelf area of the shallow marine environment, during the Late-Permian period. The Permo-Triassic Boundary (PTB), which is the end of the type-1 series, is marked by this formation’s top.

Correction to: Automation in Agriculture by Machine and Deep Learning Techniques: A Review of Recent Developments - Muhammad Hammad Saleem; Johan Potgieter; Khalid Mahmood Arif (Precision Agriculture, 2021)

Automation in Agriculture by Machine and Deep Learning Techniques: A Review of Recent Developments - Muhammad Hammad Saleem; Johan Potgieter; Khalid Mahmood Arif (Precision Agriculture, 2021)

Hydrogen Sulfide: A Novel Gaseous Molecule for Plant Adaptation to Stress - Mukhtar Ahmed; Shah Fahad; Muhammad Arif Ali; Sajjad Hussain; Muhammad Tariq; Fariha Ilyas; Shakeel Ahmad; Shah Saud; Hafiz Mohkum Hammad; Wajid Nasim; Chao Wu; Hongyan Liu (Journal of Plant Growth Regulation, 2021)

Hydrogeochemical and health risk investigation of potentially toxic elements in groundwater along River Sutlej floodplain in Punjab, Pakistan - Sajjad Ahmad; Muhammad Imran; Behzad Murtaza; Natasha; Muhammad Arshad; Rab Nawaz; Abdul Waheed; Hafiz Mohkum Hammad; Muhammad Asif Naeem; Muhammad Shahid; Nabeel Khan Niazi (Environmental Geochemistry and Health, 2021)

Using space–time scan statistic for studying the effects of COVID-19 in Punjab, Pakistan: a guideline for policy measures in regional agriculture - Sajjad Hussain; Muhammad Mubeen; Ashfaq Ahmad; Shah Fahad; Wajid Nasim; Hafiz Mohkum Hammad; Ghulam Mustafa Shah; Behzad Murtaza; Muhammad Tahir; Saima Parveen (Environmental Science and Pollution Research, 2021)

Rainfall forecasting in upper Indus basin using various artificial intelligence techniques - Muhammad Hammad; Muhammad Shoaib; Hamza Salahudin; Muhammad Azhar Inam Baig; Mudasser Muneer Khan; Muhammad Kaleem Ullah (Stochastic Environmental Research and Risk Assessment, 2021)

Strigolactone (GR24) Induced Salinity Tolerance in Sunflower (Helianthus annuus L.) by Ameliorating Morpho-Physiological and Biochemical Attributes Under In Vitro Conditions - Hira Zulfiqar; Muhammad Shahbaz; Muhammad Ahsan; Muhammad Nafees; Hammad Nadeem; Muhammad Akram; Ambreen Maqsood; Sunny Ahmar; Muhammad Kamran; Saud Alamri; Manzer H. Siddiqui; Shah Saud; et al. (Journal of Plant Growth Regulation, 2021)

Helminth protection against type-1 diabetes: an insight into immunomodulatory effect of helminth-induced infection - Muhammad Adnan Sabir Mughal; Muhammad Kasib Khan; Zaheer Abbas; Rao Zahid Abbas; Hammad ur Rehman Bajwa; Abdullah Khalid Chatha; Muhammad Imran; Zia ud Din Sindhu; Asghar Abbas; Arsalan Zafar; Muhammad Nadeem (Molecular Biology Reports, 2021)

Wind speed pattern data and wind energy potential in Pakistan: current status, challenging platforms and innovative prospects - Hammad Saulat; Muhammad Masood Khan; Muhammad Aslam; Muhammad Chawla; Sikander Rafiq; Faisal Zafar; Muhammad Mahmood Khan; Awais Bokhari; Farrukh Jamil; Abdul Waheed Bhutto; Aqeel Ahmed Bazmi (Environmental Science and Pollution Research, 2021)

RETRACTED ARTICLE: Protective effect of myricetin on nonylphenol-induced testicular toxicity: biochemical, steroidogenic, hormonal, spermatogenic, and histological-based evidences - Muhammad Umar Ijaz; Haseeb Anwar; Shabnoor Iqbal; Hammad Ismail; Asma Ashraf; Shama Mustafa; Abdul Samad (Environmental Science and Pollution Research, 2021)

New insights into the phytochemical composition, enzyme inhibition and antioxidant properties of desert cotton ( Aerva javanica (Bum.f) Shult. -Amaranthaceae) - Hammad Saleem; Gokhan Zengin; Kashif-Ur-Rehman Khan; Irshad Ahmad; Muhammad Waqas; Fawzi M. Mahomoodally; Kannan R.R. Rengasamy; Noorazwani Zainol; Syafiq Asnawi Zainal Abidin; Nafees Ahemad (Natural Product Research, 2021)

Impact of heat stress responsive factors on growth and physiology of cotton (Gossypium hirsutum L.) - Muhammad Asif Saleem; Waqas Malik; Abdul Qayyum; Sami Ul-Allah; Muhammad Qadir Ahmad; Hammad Afzal; Muhammad Waqas Amjid; Muhammad Farjad Ateeq; Zia Ullah Zia (Molecular Biology Reports, 2021)

Photocatalytic degradation of crystal violet dye under sunlight by chitosan-encapsulated ternary metal selenide microspheres - Waqar Ahmad; Adnan Khan; Nisar Ali; Sana Khan; Salah Uddin; Sumeet Malik; Nauman Ali; Hamayun Khan; Hammad Khan; Muhammad Bilal (Environmental Science and Pollution Research, 2021)

Comparative secondary metabolites profiling and biological activities of aerial, stem and root parts of Salvadora oleoides decne (Salvadoraceae) - Hammad Saleem; Irshad Ahmad; Gokhan Zengin; Fawzi M. Mahomoodally; Kashif-Ur- Rehman Khan; Hafiz Muhammad Ahsan; Syafiq Asnawi Zainal Abidin; Nafees Ahemad (Natural Product Research, 2020)

Developing the first halophytic turfgrasses for the urban landscape from native Arabian desert grass - Muhammad Zamin; Shah Fahad; Abdul Mateen Khattak; Muhammad Adnan; Fazli Wahid; Ahmad Raza; Depeng Wang; Shah Saud; Muhammad Noor; Hafiz Faiq Bakhat; Muhammad Mubeen; Hafiz Mohkum Hammad; et al. (Environmental Science and Pollution Research, 2020)

Using GIS tools to detect the land use/land cover changes during forty years in Lodhran District of Pakistan - Sajjad Hussain; Muhammad Mubeen; Ashfaq Ahmad; Waseem Akram; Hafiz Mohkum Hammad; Mazhar Ali; Nasir Masood; Asad Amin; Hafiz Umar Farid; Syeda Refat Sultana; Shah Fahad; Depeng Wang; et al. (Environmental Science and Pollution Research, 2020)

Spatial modeling of Dengue prevalence and kriging prediction of Dengue outbreak in Khyber Pakhtunkhwa (Pakistan) using presence only data - Hammad Ahmad; Asad Ali; Syeda Hira Fatima; Farrah Zaidi; Muhammad Khisroon; Syed Basit Rasheed; Ihsan Ullah; Saleem Ullah; Muhammad Shakir (Stochastic Environmental Research and Risk Assessment, 2020)

Ameliorative effect of naringin against thiram-induced tibial dyschondroplasia in broiler chicken - Xiong Jiang; Aoyun Li; Yaping Wang; Mudassar Iqbal; Muhammad Waqas; Hao Yang; Zhixing Li; Khalid Mehmood; Hammad Qamar; Jiakui Li (Environmental Science and Pollution Research, 2020)

Genetic survey of cystic echinococcosis in farm animals in Oman - Fadya Abdullah AlKitani; Senan Baqir; Muhammad Khalid Mansoor; Shumoos AlRiyami; Muhammad Hammad Hussain; Derek Roberts (Tropical Animal Health and Production, 2020)

The potential applications of picotechnology in biomedical and environmental sciences - Muhammad Zeeshan Qasim; Hafiz Mohkum Hammad; Farhat Abbas; Shafqat Saeed; Hafiz Faiq Bakhat; Wajid Nasim; Wajid Farhad; Faiz Rabbani; Shah Fahad (Environmental Science and Pollution Research, 2020)

RETRACTED ARTICLE: Trends of electronic waste pollution and its impact on the global environment and ecosystem - Rida Akram; Natasha; Shah Fahad; Muhammad Zaffar Hashmi; Abdul Wahid; Muhammad Adnan; Muhammad Mubeen; Naeem Khan; Muhammad Ishaq Asif Rehmani; Muhammadd Awais; Mazhar Abbas; Khurram Shahzad; et al. (Environmental Science and Pollution Research, 2019)

Protective effect of Astragaloside IV to inhibit thiram-induced tibial dyschondroplasia - Khalid Mehmood; Hui Zhang; Wangyuan Yao; Xiong Jiang; Muhammad Waqas; Aoyun Li; Yaping Wang; Li Lei; Lihong Zhang; Hammad Qamar; Jiakui Li (Environmental Science and Pollution Research, 2019)

RETRACTED ARTICLE: Environmental factors affecting the frequency of road traffic accidents: a case study of sub-urban area of Pakistan - Hafiz Mohkum Hammad; Muhammad Ashraf; Farhat Abbas; Hafiz Faiq Bakhat; Saeed A. Qaisrani; Muhammad Mubeen; Shah Fahad; Muhammad Awais (Environmental Science and Pollution Research, 2019)

Probabilistic seismic hazard assessment of Peshawar District, Pakistan - Ahmad Hammad Khaliq; Muhammad Waseem; Sarfraz Khan; Waqas Ahmed; Muhammad Asif Khan (Journal of Earth System Science, 2019)

Composting of municipal solid waste by different methods improved the growth of vegetables and reduced the health risks of cadmium and lead - Ghulam Mustafa Shah; Nadia Tufail; Hafiz Faiq Bakhat; Iftikhar Ahmad; Muhammad Shahid; Hafiz Mohkum Hammad; Wajid Nasim; Atika Waqar; Muhammad Rizwan; Renjie Dong (Environmental Science and Pollution Research, 2019)

Ecophysiological response of early stage Albizia lebbeck to cadmium toxicity and biochar addition - Muhammad Talha Bin Yousaf; Muhammad Farrakh Nawaz; Hammad Fayyaz Khawaja; Sadaf Gul; Shafaqat Ali; Irfan Ahmad; Fahd Rasul; Muhammad Rizwan (Arabian Journal of Geosciences, 2019)

Arsenic Level and Risk Assessment of Groundwater in Vehari, Punjab Province, Pakistan - Muhammad Shahid; Muhammad Khalid; Camille Dumat; Sana Khalid; Nabeel Khan Niazi; Muhammad Imran; Irshad Bibi; Iftikhar Ahmad; Hafiz Mohkum Hammad; Riaz Ahmad Tabassum (Exposure and Health, 2018)

Influence of composted poultry manure and irrigation regimes on some morpho-physiology parameters of maize under semiarid environments - Wajid Farhad; Mumtaz Akhtar Cheema; Hafiz Mohkum Hammad; Muhammad Farrukh Saleem; Shah Fahad; Farhat Abbas; Ikramullah Khosa; Hafiz Faiq Bakhat (Environmental Science and Pollution Research, 2018)

Potential impacts of climate change and adaptation strategies for sunflower in Pakistan - Muhammad Awais; Aftab Wajid; Muhammad Farrukh Saleem; Wajid Nasim; Ashfaq Ahmad; Muhammad Aown Sammar Raza; Muhammad Usman Bashir; Muhammad Mubeen; Hafiz Mohkum Hammad; Muhammad Habib ur Rahman; Umer Saeed; Muhammad Naveed Arshad; et al. (Environmental Science and Pollution Research, 2018)

Removal of lead from aqueous solution using polyacrylonitrile/magnetite nanofibers - Hammad Malik; Umair Ahmed Qureshi; Muhammad Muqeet; Rasool Bux Mahar; Farooq Ahmed; Zeeshan Khatri (Environmental Science and Pollution Research, 2018)

Concurrent vaccination of goats with foot and mouth disease (FMD) and peste des petits ruminants (PPR) booster vaccines - Muhammad Khalid Mansoor; Abdullmajeed Hamood Al-Rawahi; Hatim Ali El-Tahir; Badar Al-Faraei; Muhammad Hammad Hussain; Muhammad Nadeem Asi; Ibrahim Al-Hussani; Safwat Sabar (Tropical Animal Health and Production, 2018)

Regional climate assessment of precipitation and temperature in Southern Punjab (Pakistan) using SimCLIM climate model for different temporal scales - Asad Amin; Wajid Nasim; Muhammad Mubeen; Saleem Sarwar; Peter Urich; Ashfaq Ahmad; Aftab Wajid; Tasneem Khaliq; Fahd Rasul; Hafiz Mohkum Hammad; Muhammad Ishaq Asif Rehmani; Hussani Mubarak; et al. (Theoretical and Applied Climatology, 2018)

Radiation efficiency and nitrogen fertilizer impacts on sunflower crop in contrasting environments of Punjab, Pakistan - Wajid Nasim; Ashfaq Ahmad; Asad Amin; Muhammad Tariq; Muhammad Awais; Muhammad Saqib; Khawar Jabran; Ghulam Mustafa Shah; Syeda Refat Sultana; Hafiz Mohkum Hammad; Muhammad Ishaq Asif Rehmani; Muhammad Zaffar Hashmi; et al. (Environmental Science and Pollution Research, 2018)

Quantitative interpretation of carbonate reservoir rock using wireline logs: a case study from Central Luconia, offshore Sarawak, Malaysia - Hammad Tariq Janjuhah; Ahmed Mohammad Ahmed Salim; Mumtaz Muhammad Shah; Deva Ghosh; Abubaker Alansari (Carbonates and Evaporites, 2017)

From REDD+ MRV Perspective: Comparison of Two Different Forest Management Regimes Using Geospatial Techniques in Ludi Khola Watershed, Gorkha District, Nepal - Hammad Gilani; Muhammad Sohail; Upama Ashish Koju (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2017)

Effect of a bradykinin-potentiating factor isolated from scorpion venom (Leiurus quinquestriatus) on some blood indices and lipid profile in irradiated rats - Muhammad M. A. Salman; Ahmed M. Kotb; Mohie A. M. Haridy; Klaus Golka; Seddik Hammad (Molecular and Cellular Biochemistry, 2017)

Nitrogen and plant population change radiation capture and utilization capacity of sunflower in semi-arid environment - Muhammad Awais; Aftab Wajid; Muhammad Usman Bashir; Muhammad Habib-ur-Rahman; Muhammad Aown Sammar Raza; Ashfaq Ahmad; Muhammad Farrukh Saleem; Hafiz Mohkum Hammad; Muhammad Mubeen; Umer Saeed; Muhammad Naveed Arshad; Shah Fahad; et al. (Environmental Science and Pollution Research, 2017)

Agroforestry: a sustainable environmental practice for carbon sequestration under the climate change scenarios—a review - Farhat Abbas; Hafiz Mohkum Hammad; Shah Fahad; Artemi Cerdà; Muhammad Rizwan; Wajid Farhad; Sana Ehsan; Hafiz Faiq Bakhat (Environmental Science and Pollution Research, 2017)

Arsenic uptake, accumulation and toxicity in rice plants: Possible remedies for its detoxification: A review - Hafiz Faiq Bakhat; Zahida Zia; Shah Fahad; Sunaina Abbas; Hafiz Mohkum Hammad; Ahmad Naeem Shahzad; Farhat Abbas; Hesham Alharby; Muhammad Shahid (Environmental Science and Pollution Research, 2017)

Optimizing the phosphorus use in cotton by using CSM-CROPGRO-cotton model for semi-arid climate of Vehari-Punjab, Pakistan - Asad Amin; Wajid Nasim; Muhammad Mubeen; Muhammad Nadeem; Liaqat Ali; Hafiz Mohkum Hammad; Syeda Refat Sultana; Khawar Jabran; M. Habib ur Rehman; Shakeel Ahmad; Muhammad Awais; Atta Rasool; et al. (Environmental Science and Pollution Research, 2017)

Correlation studies on nitrogen for sunflower crop across the agroclimatic variability - Wajid Nasim; Hatem Belhouchette; Muhammad Tariq; Shah Fahad; Hafiz Mohkum Hammad; Muhammad Mubeen; Muhammad Farooq Hussain Munis; Hassan Javed Chaudhary; Imran Khan; Faisal Mahmood; Tauqeer Abbas; Fahd Rasul; et al. (Environmental Science and Pollution Research, 2016)

Seroprevalence of Mycobacterium avium subspecies paratuberculosis (MAP) and evaluation of risk factors in camels of the Sultanate of Oman - Muhammad Hammad Hussain; Muhammad Saqib; Mahir Gharib Al-Maawali; Salim Al-Makhladi; Mohammed Somar Al-Zadjali; Talal Al-Sidairi; Saud Asubaihi; Abdulmajeed Al-Rawahi; Muhammad Khalid Mansoor (Tropical Animal Health and Production, 2015)

Application of GIS for the identification and demarcation of selective heavy metal concentrations in the urban groundwater - Sobia Ashraf; Farhat Abbas; Muhammad Ibrahim; Umer Rashid; Shoaib Khalid; Hammad Raza Ahmad; Khalid Rehman Hakeem; Tahir Majeed (Journal of Geographical Sciences, 2015)

Cystic hydatidosis in slaughtered goats from various municipal abattoirs in Oman - Fadya Al-Kitani; Senan Baqir; Muhammad Hammad Hussain; Derek Roberts (Tropical Animal Health and Production, 2014)

Time-course changes in growth and biochemical indices of mung bean [Vigna radiata (L.) Wilczek] genotypes under salinity - Syed Hammad Raza; Muhammad Bilal Ahmad; Muhammad Arslan Ashraf; Fahad Shafiq (Brazilian Journal of Botany, 2014)

O-GlcNAc modification of the anti-malarial vaccine candidate PfAMA1: in silico-defined structural changes and potential to generate a better vaccine - Nasir Uddin; Daniel C. Hoessli; Asma Butt; Afshan Kaleem; Zeeshan Iqbal; Imran Afzal; Muhammad Hammad; Zahra Zamani; Abdul Rauf Shakoori (Molecular Biology Reports, 2012)

Formulation of anastrozole microparticles as biodegradable anticancer drug carriers - Ahmed S. Zidan; Omaima A. Sammour; Mohammed A. Hammad; Nagia A. Megrab; Muhammad D. Hussain; Manosor A. Khan; Muhammad J. Habib (AAPS PharmSciTech, 2006)